2007
DOI: 10.1016/j.cell.2007.03.051
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Ras to Phosphoinositide 3-Kinase p110α Is Required for Ras- Driven Tumorigenesis in Mice

Abstract: Ras proteins signal through direct interaction with a number of effector enzymes, including type I phosphoinositide (PI) 3-kinases. Although the ability of Ras to control PI 3-kinase has been well established in manipulated cell culture models, evidence for a role of the interaction of endogenous Ras with PI 3-kinase in normal and malignant cell growth in vivo has been lacking. Here we generate mice with mutations in the Pi3kca gene encoding the catalytic p110alpha isoform that block its interaction with Ras. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
447
2
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 536 publications
(468 citation statements)
references
References 44 publications
17
447
2
2
Order By: Relevance
“…recently been shown to be essential (Gupta et al, 2007). Here we characterize the nature of the requirement for Ras by showing that constitutively membrane-localized p110g and p110b do not require an interaction with Ras for full oncogenic activity.…”
Section: Discussionmentioning
confidence: 91%
“…recently been shown to be essential (Gupta et al, 2007). Here we characterize the nature of the requirement for Ras by showing that constitutively membrane-localized p110g and p110b do not require an interaction with Ras for full oncogenic activity.…”
Section: Discussionmentioning
confidence: 91%
“…Discs were stained for Fasciclin 3 to visualize disc outlines (blue) and for PH3 to mark cells in M-phase ((a-f) in red and (a 00 -e 00 ) and (f 0 ) in gray). PI3K signaling is low in Ras V12 , Dlg RNAi tumors From mammalian systems, it is known that Ras binds to PI3K and that oncogenic transformation in response to Ras depends on PI3K activity (Rodriguez-Viciana et al, 1994, 1997Gupta et al, 2007). In Drosophila, it was shown that PI3K is not required for physiological Ras signaling (Halfar et al, 2001;Prober and Edgar, 2002).…”
Section: Loss Of Pi3k Blocks Drosophila Tumor Growth M Willecke Et Almentioning
confidence: 99%
“…On the other hand, a recent studies using knock-in mice where the RBD of PI3K is substituted with a mutant RBD that is unable to bind Ras has shown that Ras-PI3K binding is essential for a variety of pathophysiological events, including the development of the lymphatic vasculature [42]. In endothelial cell lineages, the Ras-PI3K pathway and the internalization of vascular endothelial growth factor (VEGF) receptor 1 are involved in VEGF-dependent endothelial cell motility [43] and angiogenesis [44].…”
Section: /21mentioning
confidence: 99%
“…In endothelial cell lineages, the Ras-PI3K pathway and the internalization of vascular endothelial growth factor (VEGF) receptor 1 are involved in VEGF-dependent endothelial cell motility [43] and angiogenesis [44]. It is thus possible that a defect in the endocytosis of receptors such as VEGF receptor 3 in lymphatic endothelial cells is the cause of the impaired lymphatic development in PI3K mutant mice [42], considering the crucial role for Ras-PI3K signaling in local PIP 3 production in the endosome, as shown by this study (Fig. 5a-d and g).…”
Section: /21mentioning
confidence: 99%